EXPLORING THE ROLE OF CSR AND ORGANIZATIONAL CULTURE IN SHAPING EMPLOYEE COMMITMENT IN MALAYSIAN PRIVATE UNIVERSITIES - Fawad Ur Rehman; Farukh Sultan; Zafar Khan; Abid Rehman; Samsoor Saqib (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the influence of Corporate Social Responsibility (CSR) and organizational culture on employee commitment. Over the years, the developmental importance of CSR has grown up due to awareness of the firms’ roles in society. It is defined as the broader concept of voluntary business actions in relation to society and the environment, which has positive impacts to business’ image and relations with its stakeholders. Another concept relevant for the study is the organizational commitment which is defined as a set of attitudes the employee has towards his/her organization and it is very important for accomplishing high levels of performance and organizational turnover. The study aims to establish the ways through which CSR programs contribute to the improvement of organizational commitment by helping match the employee’s values with the organizational values of the firm. Additionally, the study investigates the role of organizational culture, defined by shared values, norms, and beliefs, in shaping employees' attitudes and behaviours. An excellent and moral organizational culture can also enhance workers’ dedication through the provision of an organizational culture that helps to clarify organizational objectives and goals. The study's findings reveal a positive correlation between robust CSR practices and higher levels of employee commitment. Furthermore, a solid organizational culture amplifies the positive effects of CSR on commitment. Therefore the research notes that there are increased chances of an organization to have a committed and productive workforce in case both CSR and supportive culture indicators are embraced. These findings offer managerial implications for the firms and institutions that seek ways to improve their socio-interactional responsibilities and employee commitment to achieving superior organizational performance outcomes. Overall, this research contributes to understanding the dynamic interplay between CSR, organizational culture, and employee commitment, offering valuable strategies for businesses to enhance their social responsibility and internal cohesion.